Exploration of Brachionus sp. Protein on the In Vivo Response of CD4 at Cantang Grouper (Epinephelus sp.) with VNN Infection (Viral Nervous Necrosis) - Nur Fauziyah Martiningsih; Uun Yanuhar; Mohammad Musa; Dwi Retna Kumalaningrum (Department of Aquaculture, 2023)
This study examines the function of Brachionus sp. protein on the Cluster Differentiation-4 (CD4) immune system in cantang grouper infected with VNN. The purpose of this study was to determine the protein content of Brachionus sp. which has the potential as an antivirus and to find out the benefits of Brachionus sp. on the expression of CD4 as an indicator of increased fish body defense system against VNN. Brachionus sp. itself contains three protein bands with molecular weights of 122.73 kDa, 75.49 kDa, and 13.77 kDa, which are expected to increase the immune system against VNN on cantang grouper. Protein injection of Brachionus with doses of 35 µl, 105 µl and 170 µl /150 g cantang grouper, showed that the lowest decrease was at a dose of 105 µl/150 gram cantang groupers.